2017
DOI: 10.1093/ije/dyx065
|View full text |Cite
|
Sign up to set email alerts
|

Early cannabis initiation and educational attainment: is the association causal? Data from the French TEMPO study

Abstract: Early cannabis can cause low educational attainment. Youths who initiate cannabis use early require attention from addiction and education specialists to reduce their odds of poor long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 79 publications
2
21
0
Order By: Relevance
“…Our finding of a potential causal relationship between adolescent cannabis use and young-adult socioeconomic status is in line with findings from multiple epidemiological studies, which have reported similar associations that survive adjustments for measured preexposure confounds as well as propensity score analyses (18,54,57,58). Indeed, comparative studies have suggested that adolescent cannabis use is a better marker for lower educational attainment than adolescent alcohol use (57).…”
Section: Discussionsupporting
confidence: 90%
“…Our finding of a potential causal relationship between adolescent cannabis use and young-adult socioeconomic status is in line with findings from multiple epidemiological studies, which have reported similar associations that survive adjustments for measured preexposure confounds as well as propensity score analyses (18,54,57,58). Indeed, comparative studies have suggested that adolescent cannabis use is a better marker for lower educational attainment than adolescent alcohol use (57).…”
Section: Discussionsupporting
confidence: 90%
“…Mechanisms of anxiety and avoidance may also explain why some students who feel uncomfortable at school miss class to consume cannabis. Longitudinal studies have confirmed participant concerns that cannabis use is associated with school absenteeism, lower educational attainment, and early school dropout (Lynskey & Hall, 2000;Melchior et al, 2017). Participants also noted that the risks of operating a vehicle or attending work while impaired may be downplayed by those who use frequently.…”
Section: Discussionmentioning
confidence: 91%
“…There are many uncertainties regarding the direction of the association between socioeconomic characteristics and cannabis use. A study published in 2017 37 shows that early cannabis initiation (≤16 years old) predicts educational attainment even when accounting for individual and family factors. Early cannabis use and educational attainment appear more strongly associated in young women than in young men.…”
Section: Cannabismentioning
confidence: 99%